CLINICAL EVALUATION OF PANIYA KSHARA IN MUTRAKRICHHA W.S.R. TO LOWER URINARY TRACT INFECTION: A CONTROLLED RANDOMISED CLINICAL TRIAL (AYUSHDHARA, 2021)
Mutrakrichha is a disease in which Mutra is voided with much Dukha (discomfort). The word Mutrakrichha comprises of two words, Mutra and Krichha, which means Krichha pravritti of Mutravahana (difficulty in micturition). Mutrakrichha comes under the disorders of Mutravaha srotas and mainly deals with Shool (pain) and Krichhata (dysuria). Mutrakrichha can be an independent disease as well as associated symptom in other disease. In the contemporary science, the disease with similar signs and symptoms are Lower urinary tract infection. Lower urinary tract infection is the most common infection known to mankind and a common condition seen in general practice. Urinary tract infection affects more than 150 million people every year worldwide. It is well explained by all the Acharyas. Charaka has described eight types of Mutrakrichha. Acharya Sushruta in Uttra-Tantra has separately described Mutraghata and Mutrakrichha. Acharyas have mentioned drugs having antibacterial and diuretic property in Mutrakrichha chikitsa. Paniya kshara is an age old treatment modality used since ancient times. To evaluate the role of Paniya kshara in Mutrakrichha, a total of thirty patients were selected with complaints of painful micturation, fever, urgency and tenderness. Patients were given Paniya Kshara. The study revealed highly significant results in terms of pain, fever, urgency and tenderness.